2010
DOI: 10.1038/sc.2010.13
|View full text |Cite
|
Sign up to set email alerts
|

Impaired immune response to voluntary arm-crank ergometer exercise in patients with cervical spinal cord injury

Abstract: Study design: Non-randomized study. Objective: The mechanism underlying exercise-induced argumentation of natural killer cell cytotoxic activity (NKCA) in humans remains unclear. To address this, NKCA responses were studied during and after exercise in persons with cervical spinal cord injury (CSCI) and dysfunctional sympathetic nervous system. Setting: Kibikogen Rehabilitation Center for Employment Injuries. Methods: We examined the NKCA responses to 20-min arm-crank ergometer exercise at 60% of maximum oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…This deficit results in limitation of the peak heart rate in CSCI and often such subjects can neither complete intense exercise nor exercise longer than 20 min at 60% of VO 2 max, as demonstrated in our previous study. 7 Therefore, the subjects of the present study, that is, the wheelchair half marathon athletes with CSCI, who completed the race in about 80-110 min, are different to those who participated in our previous study. 7 In summary, the present study demonstrated that the wheelchair half-marathon race resulted in increase of NKCA despite the lack of increase in plasma adrenaline concentration in CSCI athletes.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…This deficit results in limitation of the peak heart rate in CSCI and often such subjects can neither complete intense exercise nor exercise longer than 20 min at 60% of VO 2 max, as demonstrated in our previous study. 7 Therefore, the subjects of the present study, that is, the wheelchair half marathon athletes with CSCI, who completed the race in about 80-110 min, are different to those who participated in our previous study. 7 In summary, the present study demonstrated that the wheelchair half-marathon race resulted in increase of NKCA despite the lack of increase in plasma adrenaline concentration in CSCI athletes.…”
Section: Discussionmentioning
confidence: 77%
“…7 Therefore, the subjects of the present study, that is, the wheelchair half marathon athletes with CSCI, who completed the race in about 80-110 min, are different to those who participated in our previous study. 7 In summary, the present study demonstrated that the wheelchair half-marathon race resulted in increase of NKCA despite the lack of increase in plasma adrenaline concentration in CSCI athletes. The intensity of the wheelchair half-marathon race activates NKCA in athletes with CSCI between C6 and C8, through mechanisms other than circulating adrenaline concentrations.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations